Transformational Leadership and Organizational Citizenship Behavior: Moderating the Organizational Climate - Wirtadipura, Dian; Wahyudi (Yayasan Inovasi Kemajuan Intelektual, 2025)
During rapid organizational change and increasingly complex work demands, leaders are no longer just able to direct; they must be able to inspire. Transformational leadership is a leadership style that drives performance and ignites employees’ enthusiasm to go beyond the limits of their formal roles through OCB. This study aims to analyse the influence of TL on OCB behaviour and test the role of OC as a moderator variable in the relationship. This study uses a quantitative approach with the PLS-SEM method and involves 130 respondents from PT. Krakatau Tirta Industri. The data collection instrument was a Likert scale questionnaire, analyzed using SmartPLS 4 software. The results showed that TL had a positive and significant effect on OCB (β = 0.213; t = 2.131; p = 0.033), as well as OC on OCB had a positive and significant effect (β = 0.678; t = 6.920; p = 0.000). In addition, it was found that OC moderated the relationship between TL and OCB significantly (β = 0.058; t = 2.127; p = 0.030), suggesting that in supportive OC, the influence of TL on OCB became stronger. Likewise, the R² value of 80.3% provides evidence that TL and OC, along with their interactions, are strong and relevant predictors of OCB levels. The theoretical implications of these findings underscore the importance of integrating contextual organisational factors in the study of leadership effectiveness and encouraging organisations to create an empowering work environment to optimise employee voluntary contributions. These findings also enrich the literature on organisational behaviour by demonstrating how leadership dimensions and work climate interact to shape positive behaviour in the workplace.